The Role of Green Supply Chain Management in Predicting Indonesian Firms' Performance: Competitive Advantage and Board Size Influence - Maya Novitasari; Ali Saleh Alshebami; M. Agus Sudrajat (Universitas Pasundan, 2021)
This study examines the effect of green supply chain management (GSCM) on firm performance, with competitive advantage as mediation and board size as moderation. Purposive sampling method was used to examine 516 PROPER companies from 2010 to 2018. Data were obtained from the Indonesia Stock Exchange. Results show that GSCM has a positive effect on competitive advantage but does not affect firm performance, whereas competitive advantage has a positive effect on firm performance. Moreover, competitive advantage can mediate the relationship between GSCM and firm performance. Board size cannot moderate the relationship between GSCM and competitive advantage, but it can moderate the relationship between competitive advantage and firm performance and the relationship between GSCM and firm performance. The results of this study can be used to improve firm performance of companies concerned with environmental impact. The research findings contribute to the idea that board size has a role in strengthening the implementation of GSCM to create competitive advantages that can increase firm performance.